Nazam ratap Fatimah: Dari rumah duka ke surau - Zuriati (Universiti Kebangsaan Malaysia, 2007)
Nazam Ratap Fatimah is a Minangkabau manuscript with religious (Islam) content that differs from mainstream traditions. It was not re-written or copied to enhance Islamic education in suraus, nor was it written to be read according to the maratok tradition at the rumah duka (death house). Though forbidden by Islam, it was nevertheless brought from the death house to the surau. The intensity of tasawuf (Sufism) elements in it shows that it was written by a Sufi, probably someone from among the Kaum Tua (Old Generation) in Minangkabau. The manuscript is meant as a textbook for Islamic education, but with the death house as the school. That is the important method employed by the Kaum Tua to limit the maratok tradition